Philotypes of intestinal microbiotes in patients with arterial hypertension and abdominal obesity - S. M. Koval; I. O. Snihurska; K. O. Yushko (Zaporozhye State Medical University, 2020)
The aim: to study the content of the main phylotypes of the gut microbiota (GM) (Firmicutes, Bacteroidetes and Actinobacteria) in residents of Ukraine - patients with arterial hypertension (AH), which occurs against the background of abdominal obesity (AO) and metabolic disorders. Materials and methods. 70 patients (residents of Ukraine) with AH stage II, 2-3 degrees (46 patients with AO and 24 with normal body weight (NBW)) were examined. The control group consisted of 20 practically healthy individuals. The survey included standard clinical, laboratory and instrumental methods. The content of the main GM phylotypes was determined by identifying the total bacterial DNA and DNA of Firmicutes, Bacteroidetes and Actinobacteria using the method of quantitative real-time polymerase chain reaction. Statistical analysis of the data was carried out using standard methods using Microsoft Excel 17.0. Results. In patients with AH in combination with AO, residents of Ukraine, significant differences were revealed in the relative content of the main phylotypes of GM, both in comparison with healthy individuals and patients with AH and NBW: a significant increase in the relative content of Firmicutes compared with the control group and a significant increase in the ratio of Firmicutes/Bacteroidetes in comparison with practically healthy individuals and with hypertension patients with NBW. In addition, in AH patients with AO, in contrast to AH patients with NBW, it was found that changes in the GM composition at the level of their main phylotypes are associated with the presence of prediabetes, an insulin resistance (IR) index, and the level of low-density lipoprotein cholesterol in the blood. Conclusions. The results of this study indicate that changes in GM can play a significant role in the pathogenesis of AH and AO in residents of Ukraine.